1996
DOI: 10.1002/actp.1996.010470202
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and microwave‐activate non‐aqueous free‐radical dispersion polymerization of methyl methacrylate in n‐heptane

Abstract: Thermal and microwave-induced free-radical non-aqueous dispersion polymerization of methyl methacrylate (MMA) in the presence of poly(styrene)-block-poly(ethene-alt-propene) dispersing agent were compared. For controlled polymerization in the microwave field, a new microwave polymerization reactor was built to afford uniform heating and to control temperature via microwave power variation. At identical MMA concentration and polymerization temperature of70 "C no special effect of the microwave field on convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…In this context, it is worth mentioning that Mülhaupt and coworkers observed no difference in terms of molecular weights, polydispersities, stereoregularities, particle sizes, and particle-size distributions between conventional and microwave heating for the dispersion polymerization of methyl methacrylate in heptane. [142] The corresponding experiments were performed in a specially equipped microwave reactor (cf. reference [78] and Figure 8).…”
Section: Emulsion Polymerizationsmentioning
confidence: 99%
“…In this context, it is worth mentioning that Mülhaupt and coworkers observed no difference in terms of molecular weights, polydispersities, stereoregularities, particle sizes, and particle-size distributions between conventional and microwave heating for the dispersion polymerization of methyl methacrylate in heptane. [142] The corresponding experiments were performed in a specially equipped microwave reactor (cf. reference [78] and Figure 8).…”
Section: Emulsion Polymerizationsmentioning
confidence: 99%
“…thermal microwave effect can be observed in some microwave-assisted polymerizations. [10][11][12] Very recently, Schubert et al demonstrated that the cationic ROP of 2-oxazoline and its derivatives was accelerated under a superheated condition by conventional heating, although a similar acceleration induced by microwave heating (MH) had previously been observed. [12][13][14][15] Similarly, we revealed that the enhancement of flash conventional heating (FCH) on the ROP of e-CL with Sn(Oct) 2 as a catalyst, matched well that seen with MH.…”
Section: Introductionmentioning
confidence: 99%
“…Only during the last several years, polymer chemists have discovered the advantages of microwave irradiation as well 4,5. The effect of microwave irradiation has been mainly investigated for step‐growth polymerizations,6,7 ring‐opening polymerizations,8–10 and for both free and controlled radical polymerizations 11–13. Contradictory reports on the (non‐)existence of microwave effects have been reported for both the ring‐opening polymerization of ε ‐caprolactone (e.g.…”
Section: Introductionmentioning
confidence: 99%